2005
DOI: 10.1111/j.1468-3156.2004.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion, social networks and ethnicity: the development of the Social Inclusion Interview Schedule for young people with learning disabilities

Abstract: The paper reports on the development and piloting of the Social Inclusion Interview Schedule (SIIS). This uses pictures to explore social networks and feelings of social inclusion. The background, conceptual framework and development of the interview schedule are discussed and interim findings are highlighted. The challenge of not just identifying the constituents of a social network but also attributing some measure of intensity to the relationships and activities identified will be considered. The study site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…They discovered the meaning of their existence by interacting in mutual relationships with others (Hunter & Jordan, 2010). This is consistent with the findings of Pawson et al (2005), in that people feel socially included when social relationships are characterised by intimacy and mutual sympathy, not just when systemic discrimination has been abolished. Rimmerman (2013) also reports that positive interaction within the community is an important factor that leads to feelings of belonging or social inclusion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They discovered the meaning of their existence by interacting in mutual relationships with others (Hunter & Jordan, 2010). This is consistent with the findings of Pawson et al (2005), in that people feel socially included when social relationships are characterised by intimacy and mutual sympathy, not just when systemic discrimination has been abolished. Rimmerman (2013) also reports that positive interaction within the community is an important factor that leads to feelings of belonging or social inclusion.…”
Section: Discussionsupporting
confidence: 89%
“…Hall suggested a social inclusion agenda that emphasises social accommodation, relationships, participation in activities, dwellings, employment, support from service providers, social support, individual ability, others' attitudes, action, and awareness. Pawson, Raghavan, Small, Craig, and Spencer (2005) suggested an agenda of social inclusion that emphasises action, decision-making, networking, feelings of solidarity, and hope about the future for people with intellectual disabilities. They found that people with intellectual disabilities find positive meaning by participating in diverse activities involving their social network, school, workplace, area day care centers, and universities.…”
Section: The Elements Of Social Inclusionmentioning
confidence: 99%
“…Thus findings from more disaffected or excluded minorities, for example, BodenAlbala et al (2005), may not translate to the present study. Pawson, Rahgavan, and Small (2005) make the further point that the social network of a person of ethnic minority will reflect how well-established and numerous that minority is in the person's neighbourhood.…”
Section: Discussionmentioning
confidence: 99%
“…Items focused on the carer's perception of the young person's social world and future options. The interview was piloted with a small group of family carers (see Pawson et al . 2005).…”
Section: Methodsmentioning
confidence: 99%